The Benefits of a Dental Operating Microscope for Tooth Extractions: A Case Report - Bruno Calkovsky; Ladislava Slobodnikova; Sarah Kalmanova; Maria Janickova (Dentistry Journal, 2025)
Background/Objectives: Operating microscopes are becoming increasingly common tools in dentistry and dentoalveolar surgery due to their ability to enhance procedural precision and control. This case report aims to highlight the benefits of the operating microscope in minimizing surgical trauma and improving clinical outcomes during tooth extractions. Methods: Three clinical cases involving potentially complicated tooth extractions were treated using a dental operating microscope. The procedures were performed without flap elevation, extensive bone removal, or suturing, with the goal of reducing trauma to adjacent structures. Results: In all three cases, the use of the microscope facilitated minimally invasive extractions. The surrounding tissues were preserved, and the patients experienced uneventful healing. Clinical re-evaluation was performed several weeks postoperatively to confirm mucosal healing and absence of complications. Conclusions: The dental operating microscope allowed for precise, minimally traumatic extractions, resulting in favorable healing outcomes. Although limited, current literature and the presented cases suggest promising results and superior outcomes when incorporating a microscope into dentoalveolar surgical practice. This case report further supports the role of magnification in improving surgical precision and patient care.